Comparison of Clinical Examination and Various Imaging Modalities in the Diagnosis of Head and Neck Cancer - Uwe Schneider; Inse Graß; Martin Laudien; Joachim Quetz; Hendrik Graefe; Barbara Wollenberg; Jens Eduard Meyer (International Archives of Otorhinolaryngology, 2021)
Introduction Squamous cell Carcinoma of the Head and Neck (HNSCC) is the most common tumor entity of malignant processes in the head and neck area. Due to the metastasizing behavior of these tumors, the staging is indispensable for the treatment planning and requires imaging techniques, which are sensitive, specific, and as far as possible cost-effective, to benefit ultimately the patient and to ensure optimal care. Objectives The aim of the present study is to compare the clinical examination including palpation, ultrasound and computed tomography (CT)/magnetic resonance imaging (MRI) for the diagnosis of neck metastases to make the correct indication for a neck dissection. Methods Data from 286 patients with HNSCC were analyzed for neck metastases to determine which diagnostic tool is the best to answer the question if a neck dissection is necessary or not. Each study method was examined retrospectively by comparing sensitivity, specificity, the positive/negative predictive value, the positive likelihood ratio and the diagnostic accuracy. Results The ultrasound showed a sensitivity of 91.52%, a specificity of 61.67%, a positive/negative predictive value of 76.65%/84.09%, a positive likelihood ratio of 2.39 and a diagnostic accuracy of 78.95%. The clinical examination showed a sensitivity of 75.76%, a specificity of 66.12%, a positive/negative predictive value of 75.30%/66.67%, a positive likelihood ratio of 2.24 and a diagnostic accuracy of 71.68%. The CT/MRI showed a sensitivity of 78.66%, a specificity of 62.50%, a positive/negative predictive value of 74.14%/68.18%, a positive likelihood ratio of 2.10 and a diagnostic accuracy of 71.83%. Radiographically, ultrasound, as well as the clinical examination, could be judged to be free from radiation load and side effects from the contrast medium. The high dependence on the investigator when using ultrasound made reproducibility of the results difficult. Conclusions It could be shown that ultrasound was the diagnostic tool with the highest sensitivity, positive/negative predictive value, positive likelihood ratio and diagnostic accuracy by detecting and interpreting metastases in the head and neck region correctly. Whether a neck dissection should be performed depends to a large extent on the ultrasound findings.